rMBP-NAP Suppresses OXA-induced Allergic Dermatitis by Regulating the Th1/Th2 Balance - Hao Zheng; Qiaozhen Kang; Chenglong Zhang; Lu Yang; Xin Liu (Iranian Journal of Immunology, 2023)
Background: Allergic dermatitis (AD) is an inflammatory skin disease that arises from abnormal T lymphocyte activation. A recombinant fusion protein comprising Helicobacter pylori neutrophil-activating protein and maltose binding protein, rMBP-NAP, has been documented as a novel immunomodulatory TLR agonist.Objective: To explore the effect of the rMBP-NAP on the OXA-induced AD in a mouse model and clarify the possible action mechanism.Methods: The AD animal model was induced by repeated administration of oxazolone (OXA) in BALB/c mice. H&E staining was used to analyze the ear epidermis thickness and the number of infiltrating inflammatory cells. TB staining was used to detect mast cell infiltration in the ear tissue. ELISA was used to analyze the secretion of cytokines IL-4  and IFN-γ in peripheral blood. qRT-PCR was used to determine the expression levels of IL-4, IFN-γ, and IL-13 in ear tissue.Results: OXA induced the establishment of an AD model. After the rMBP-NAP treatment, the thickness of the ear tissue and the number of mast cells infiltrated in AD mice reduced, and the serum and ear tissue levels of IL-4 and IFN-γ increased, but the ratio of IFN-γ (rMBP-NAP group)/IL-4 (rMBP-NAP group) was greater than the ratio of IFN-γ (sensitized group)/IL-4 (sensitized group).Conclusion: The rMBP-NAP improved the disease symptoms including skin lesions in AD, alleviated the inflammation in ear tissue, and restored the Th1/2 balance by inducing a shift from the Th2 to the Th1 response. The results of our work support the use of rMBP-NAP as an immunomodulator for AD treatment in future investigations.